Kesiapan Guru PAI dalam Evaluasi Pembelajaran Berbasis Cinta - Isnawati Nur Afifah Latif; Rifa‘Afuwah; Muslimin Muslimin; Abdulloh Safiq; Rr. Kusuma Dwi Nur Ma'rifati (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study describes the readiness of Islamic Education teachers to implement love-based assessment in madrasahs in East Java. The study used a descriptive quantitative survey involving 24 Islamic Education teachers from three madrasahs selected through purposive sampling based on level, location, and institutional status. Data were collected using a 40-item Likert questionnaire covering pedagogical assessment competence, conceptual understanding of love-based assessment, affective readiness, and assessment instrument availability. The instrument showed strong reliability with a Cronbach's Alpha value of 0.87, and the data were analyzed using percentages, means, and readiness categories. The findings show that teachers' overall readiness reached 68.7 percent, which falls into the moderately ready category. Urban public madrasahs obtained higher readiness scores than a rural private madrasah, while the availability of affective and spiritual assessment instruments became the weakest dimension. These results imply that love-based assessment in Islamic Education needs systematic professional development, contextual assessment instruments, and stronger institutional support so that cognitive, affective, social, and spiritual learning outcomes can be evaluated more humanely.